Quelle place pour le citoyen dans les processus de qualification environnementale des entreprises ? - Nathalie Semal (Développement Durable et Territoires)
Sustainable development aims to integrate stakeholder negotiation into economical reasoning and acting models. The stakeholder theory translates this approach in the economics field. Some tools like ISO 14001 standard crystallise this theory. But the practical ways of its implementation do not allow a balanced integration of the hole range of stakeholders views. Stakeholder dialog, which aims to build a consensus about enterprises “environmental quality”, is mostly negotiated inside the economic space. ISO 14001 standardisation system is not likely to allow stakeholder negotiation rights integration while citizens do not organise an environmental quality watching over network.